2003
DOI: 10.2169/internalmedicine.42.263
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Inflammatory Fibroid Polyp Treated with Helicobacter pylori Eradication Therapy

Abstract: Gastric inflammatory fibroid polyps (IFPs) are rare benign lesions that occur in the distal stomach. We describe a 70-year-old womanwith Helicobacter pyloripositive gastric IFP treated with eradication. Gastroduodenal endoscopy revealed a pyramidal-shaped, broadbased tumor with an ulcerated apex at the antrum.Helicobacter pylori was positive by both histology and tissue culture, and eradication (a proton pump inhibitor, amoxicillin, and clarithromycin) was performed. After 3 months, the tumor morphologically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 10 publications
(6 reference statements)
1
10
1
1
Order By: Relevance
“…H. pylori infection is commonly seen associated with hyperplastic polyps of the stomach. Hyperplastic polyps will regress through programmed cell death after early eradication of H. pylori (68)(69)(70). Hyperplasia of bronchial epithelium in chronic bronchitis caused by infection might regress by apoptosis after elimination of infection (27).…”
Section: Regression Of Residual Cystsmentioning
confidence: 99%
“…H. pylori infection is commonly seen associated with hyperplastic polyps of the stomach. Hyperplastic polyps will regress through programmed cell death after early eradication of H. pylori (68)(69)(70). Hyperplasia of bronchial epithelium in chronic bronchitis caused by infection might regress by apoptosis after elimination of infection (27).…”
Section: Regression Of Residual Cystsmentioning
confidence: 99%
“…In this case, it was covered almost completely by normal mucosa. It has been suggested that H. pylori may play a role in the pathophysiology of IFP, however, tests for H. pylori were negative in this case [7]. IFP was strongly suspected based on the findings on endoscopic ultrasonography in this case, and the lesion was resected by ESD.…”
Section: Discussionmentioning
confidence: 82%
“…There have been reported associations with chronic atrophic gastritis, but often times the adjacent mucosa is normal [4]. It has been suggested by Nishiyama et al, that there is a relationship between H. Pylori and the development and treatment of inflammatory fibroid polyps [7]. No conclusions have been made as other cases, including the one presented above, have not shown an association with H. pylori [8].…”
Section: Discussionmentioning
confidence: 91%